REFORMASI PAJAK DALAM RANGKA MENINGKATKAN PENDAPATAN NEGARA - Niru Anita Sinaga (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2017)
Abstract:One of the goals of the state of Indonesia lies in the Preamble of the 1945 Constitution of the State of the Republic of Indonesia, namely shall protect the whole Indonesian nation and the entire native land of Indonesia and to advance the public welfare, to educate the life of the nation, and the participate in the execution of world order which is by virtue of freedom. One of the way to make it happen is through development in all fields equally both materially and spiritually. Development requires funds, one source through tax collection. Tax is a mandatory contribution to the state that is owed by an individual or entity that is compelling based on law, by not obtaining direct remuneration and used for the purposes of the state for the greatest possible prosperity of the people. In general tax functions: Financially, regulate, stability, and redistribution of funding. The principle and theory of tax collection, among others: Justice, legal philosophy, economics, and finance. Terms of tax collection must meet the requirements of justice, juridical, economic, financial and the collection system should be simple. In order for tax collection to work properly, regulations on taxation have been established. But in practice often experience problems. The discussion in this study is to discuss about: